2018
DOI: 10.1002/anie.201804006
|View full text |Cite
|
Sign up to set email alerts
|

Chromophore Activation of α,β‐Unsaturated Carbonyl Compounds and Its Application to Enantioselective Photochemical Reactions

Abstract: The first law of photochemistry, as described by Theodor von Grotthuß and John W. Draper, states that only the light absorbed by the irradiated matter can effect photochemical change. Consequently, the photochemical behavior of a molecule can be controlled by bringing its absorbance properties in line with the emission of the light source. A compound with a chromophore that only absorbs light at short wavelengths will not be excited by light of longer wavelengths. If one can reversibly modify the photophysical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
67
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 104 publications
(71 citation statements)
references
References 114 publications
0
67
0
1
Order By: Relevance
“…After initial work by Hammond with as ensitizer that was later shown to operate on the singlet hypersurface, [2] Ouanns and co-workers found in 1973 that chiral ketone 2 induced an otable but small enantioselectivity (3 % ee)i nt he formation of 1 (Scheme 1). [12,13] In the current study,weattempted to use catalyst 4 in an enantioselective [14] di-p-methane rearrangement reaction [15] of 3-allyl-substituted quinolones.A lthough the enantioselectivities of the reaction remained moderate,the mode of action turned out to be remarkable.I tw as found that the enantioenriched cyclopropanes are formed in ad eracemization process,w hich resembles the seminal work on chiral cyclopropanes [2,3] (see Scheme 1), and which likely proceeds via a1 ,3-diradical intermediate.T he results of our preliminary experiments are summarized in this Communication.Initial experiments were performed with quinolone 5a, which was readily obtained from the respective methyl (2-chloro-7-benzyloxyquinolin-3-yl)acetate by double amethylation, reduction to the aldehyde,m ethylenation, and final hydrolysis of the 2-chloroquinolone (see the Supporting Information for further details). [4,5] The few reported studies were discouraging,a nd enantioselectivities did not exceed 20 % ee.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…After initial work by Hammond with as ensitizer that was later shown to operate on the singlet hypersurface, [2] Ouanns and co-workers found in 1973 that chiral ketone 2 induced an otable but small enantioselectivity (3 % ee)i nt he formation of 1 (Scheme 1). [12,13] In the current study,weattempted to use catalyst 4 in an enantioselective [14] di-p-methane rearrangement reaction [15] of 3-allyl-substituted quinolones.A lthough the enantioselectivities of the reaction remained moderate,the mode of action turned out to be remarkable.I tw as found that the enantioenriched cyclopropanes are formed in ad eracemization process,w hich resembles the seminal work on chiral cyclopropanes [2,3] (see Scheme 1), and which likely proceeds via a1 ,3-diradical intermediate.T he results of our preliminary experiments are summarized in this Communication.Initial experiments were performed with quinolone 5a, which was readily obtained from the respective methyl (2-chloro-7-benzyloxyquinolin-3-yl)acetate by double amethylation, reduction to the aldehyde,m ethylenation, and final hydrolysis of the 2-chloroquinolone (see the Supporting Information for further details). [4,5] The few reported studies were discouraging,a nd enantioselectivities did not exceed 20 % ee.…”
mentioning
confidence: 99%
“…[8] Am odified version of the xanthone catalyst used in this and related studies [9] was presented in 2014 and was based on at hioxanthone as the sensitizing unit. [12,13] In the current study,weattempted to use catalyst 4 in an enantioselective [14] di-p-methane rearrangement reaction [15] of 3-allyl-substituted quinolones.A lthough the enantioselectivities of the reaction remained moderate,the mode of action turned out to be remarkable.I tw as found that the enantioenriched cyclopropanes are formed in ad eracemization process,w hich resembles the seminal work on chiral cyclopropanes [2,3] (see Scheme 1), and which likely proceeds via a1 ,3-diradical intermediate.T he results of our preliminary experiments are summarized in this Communication. [12,13] In the current study,weattempted to use catalyst 4 in an enantioselective [14] di-p-methane rearrangement reaction [15] of 3-allyl-substituted quinolones.A lthough the enantioselectivities of the reaction remained moderate,the mode of action turned out to be remarkable.I tw as found that the enantioenriched cyclopropanes are formed in ad eracemization process,w hich resembles the seminal work on chiral cyclopropanes [2,3] (see Scheme 1), and which likely proceeds via a1 ,3-diradical intermediate.T he results of our preliminary experiments are summarized in this Communication.…”
mentioning
confidence: 99%
“…As mentioned in the introduction, Lewis acids display a profound influence on the absorption properties of enones . Figure shows the absorption spectrum of enone 5 a in dichloromethane solution ( c= 0.5 m m ).…”
Section: Resultsmentioning
confidence: 92%
“…In both cases, there is a significant absorption at longer wavelength that exceeds in terms of quantitative absorbance the n–π* absorption of the uncomplexed substrate 5 a . In the presence of a Lewis acid there is no n–π* transition …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation